Domestic Violence and Community Safety in Nepal: Evidence from the Nepal Living Standards Survey IV - K.C., Dipendra (Nepalese Journal of Society and Culture, 2025)
Domestic violence refers to physical, sexual, emotional and psychological abuse perpetrated by intimate partners or family members within the household setting. It represents a critical violation of human rights with severe health and social consequences. The problem of domestic violence remains essential to the field of health and social justice in Nepal; however, extensive empirical data covering the prevalence and features of domestic violence is limited. This paper studies the trends of domestic violence and perceptions towards community safety using a national sample from the Nepal Living Standards Survey IV (2022-23), a nationally representative survey of 9,600 households across all seven provinces. The analysis employs bivariate analysis to examine initial associations between variables, followed by multivariate logistic regression models to control for confounding factors while focusing on the social, economic and safety status of households to correlate them with the prevalence of violence within modern Nepalese society. Although legal frameworks have changed considerably, implementation difficulties and issues with cultural acceptance continue to undermine violence prevention efforts. The multivariate analysis revealed that household poverty, lower educational attainment of women, rural residence and traditional gender attitudes were significant predictors of domestic violence prevalence, even after controlling for demographic variables. The findings indicate that economic empowerment programs, educational initiatives targeting gender equality and community-based interventions addressing cultural norms show promise for violence reduction. This discussion provides necessary evidence for designing targeted social work interventions and policy frameworks within the dynamic social environment that characterizes Nepal.